Effect of Constriction Oscillation on Flow for Potential Application to Vocal Fold Mechanics: Numerical Analysis and Experiment - Toru HYAKUTAKE; Shinji DEGUCHI; Akiya SHIOTA; Yasunobu NISHIOKA; Shinichiro YANASE; Seiichi WASHIO (Journal of Biomechanical Science and Engineering, 2006)
Oscillation of the vocal folds makes a sound source of the human voiced sound. Understanding of the oscillation mechanism, which is a complex flow-structure interaction problem in the airway, is crucial for considering clinical diagnosis of voice disorders. However, details of the oscillation mechanism are still unclear partly because, from a fluid mechanical viewpoint, the effect of oscillation of the vocal fold wall during the phonation on airflow behaviors remains elusive. In the present study, flow characteristics in a sinusoidally-oscillating constriction mimicking the vocal fold were investigated by numerical and experimental approaches. The numerical analyses focused in particular on the effect of constriction oscillation on flow separation demonstrated that the flow separation point moves continuously and periodically in a frequency-dependent manner. In the experimental study, an apparatus was newly designed, with a view to detect the oscillation-induced movement of the flow separation point, to enable detailed measurement of pressure distribution along the constriction with an interval of 2 mm that is synchronized with measurement of constriction displacement. Although movement of the separation point as seen in the numerical analyses was not detected by this limiting resolution of the apparatus, we obtained pressure-width relations that is partly contrary to the numerical results but is presumably dependent on the inlet boundary condition. These findings indicate that appropriate evaluations of separation point and inlet boundary conditions are key factors to characterize the flow in oscillating constriction, which is crucial for better understanding of the vocal fold mechanics.